EKSPOSISI TAFSIR KH. MAIMOEN ZUBAIR DALAM BINGKAI TAFSIR MODERN: Sebuah Pembacaan Melalui Perspektif Kesarjanan Barat - Saichul Anam (AL ITQAN: Jurnal Studi Al-Qur'an, 2024)
This research aims to examine whether the pesantren interpretation, particularly the interpretation of KH. Maimoen Zubair in Safīnah Kallā Saya’lamūn, is still trapped in textuality and repetition, and to position this interpretation within the typology of modern exegesis. Using a qualitative method based on content analysis, this study maps the characteristics of KH. Maimoen Zubair’s exegesis in relation to the needs of the modern Muslim community and measures it against the framework of modern exegesis as mapped by J.M.S. Baljon, J.J.G. Jansen, Johanna Pink, Pieter Coppens, and Mun’im Sirry. The results of the study indicate that KH. Maimoen Zubair’s exegesis successfully breaks free from the textuality and repetition often associated with pesantren interpretations. His interpretations respond to contemporary issues such as environmental exploitation, Quran translation, and technological development, offering practical and relevant solutions. Additionally, within the framework of modern exegesis, this interpretation is classified as "orthodox yet modern," integrating traditional approaches with a progressive and adaptive vision for addressing contemporary challenges. This study affirms that pesantren exegesis has great potential to become a dynamic and contextual space for interpretation, contributing significantly to the discourse of modern exegesis while remaining rooted in traditional values.